2017
DOI: 10.1111/cbdd.13152
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cytotoxicity and apoptosis by raloxifene in combination with estrogen and methotrexate in human endometrial stromal cells

Abstract: Endometrial hyperplasia is a condition that may lead to the development of endometrial carcinoma. Initially, changes of the endometrium are caused by the estrogen's hyperstimulation that may lead to the development of an irregular bleeding and the infertility problems. Therapy of endometrial hyperplasia is limited to medical and surgical approaches. During the past decade, the new types of drugs were developed for the treatment of the endometrial hyperplasia. Here, for the first time, we investigated the cytot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Takacs et al [21] reported that the success rate of methotrexate showed significant variability at values below and above 12 mm of the endometrium. In fact, Nikolic et al [22] reported that low-dose methotrexate can be used together with raloxifene in the treatment of endometrial hyperplasia. As a opposing view, Taş et al [9] investigated the efficacy of a single dose of methotrexate, but reported that endometrial thickness was not a determining factor in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Takacs et al [21] reported that the success rate of methotrexate showed significant variability at values below and above 12 mm of the endometrium. In fact, Nikolic et al [22] reported that low-dose methotrexate can be used together with raloxifene in the treatment of endometrial hyperplasia. As a opposing view, Taş et al [9] investigated the efficacy of a single dose of methotrexate, but reported that endometrial thickness was not a determining factor in their study.…”
Section: Discussionmentioning
confidence: 99%